2013
DOI: 10.1111/gtc.12062
|View full text |Cite
|
Sign up to set email alerts
|

Unperverted synthesis of complex sphingolipids is essential for cell survival under nitrogen starvation

Abstract: Changes in membrane dynamics are known to occur in cells faced with starvation. However, the functions of the major lipid components of biological membranes, sphingolipids, during the starvation response remain unclear. In this study, we found that yeast cells lacking genes encoding mannosylinositol phosphorylceramide (MIPC) synthases (csg1D csh1D) underwent rapid cell death upon nitrogen starvation, but not upon carbon starvation or carbon and nitrogen starvation. Addition of NaN 3 prevented the nitrogen star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…This is consistent with the observation that mutations in genes involved in amino acid biosynthesis or nitrogen uptake influence the life span [7]. Nitrogen limitation has been linked to ROS increase and promotes autophagy induction [8, 9] by the sphingolipids biosynthetic pathway [10, 11]. The relative concentration of each available amino acid also affects yeast longevity [7, 1215] as well as the ratio of essential to nonessential amino acids [16].…”
Section: Cr In Yeastsupporting
confidence: 79%
“…This is consistent with the observation that mutations in genes involved in amino acid biosynthesis or nitrogen uptake influence the life span [7]. Nitrogen limitation has been linked to ROS increase and promotes autophagy induction [8, 9] by the sphingolipids biosynthetic pathway [10, 11]. The relative concentration of each available amino acid also affects yeast longevity [7, 1215] as well as the ratio of essential to nonessential amino acids [16].…”
Section: Cr In Yeastsupporting
confidence: 79%
“…Our results are consistent with a previous report that (csg1Δ csh1Δ) cells lacking enzymatic activity to mannosylate IPC die upon nitrogen deprivation. 17 Consistent with accumulating ROS, csg2Δ cells have increased sensitivity to oxidative stress (Supplementary Figure 1C). As loss of Csg2 causes a block in a late step in the sphingolipid synthesis pathway (diagrammed in Figure 1c), a genetic approach was taken to determine whether cell death is associated with accumulation of upstream sphingolipid precursors (quantitated by mass spectrometry in Figure 2b below) or loss of downstream complex sphingolipids.…”
Section: Resultsmentioning
confidence: 85%
“…S1). The Ca 2+ supersensitivity of MIPC synthesis-deficient mutants is caused by the accumulation of IPC-C (Beeler et al, 1998;Zhao et al, 1994), and the cell death under nitrogen starvation due to the loss of MIPC synthesis is rescued by the deletion of SUR2 or myriocin, both of which prevent the accumulation of IPC-C (Yamagata et al, 2013). However, the growth defect of sur1D csh1D vma2D cells at pH 7.2 was not suppressed on the deletion of SUR2 or SCS7 (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, fluorescence recovery after photobleaching (FRAP) analysis revealed that loss of SCS7 and/or SUR2 affects the lateral diffusion of membrane proteins (Uemura et al, 2014). Loss of MIPC synthesis causes supersensitivity to Ca 2+ (Uemura et al, 2003;Zhao et al, 1994), rapid cell death under nitrogen starvation (Yamagata et al, 2013), and impairment of a specific endosomal trafficking pathway and cell integrity (Tani & Kuge, 2010, 2012Morimoto & Tani, 2015). In addition, MIPC regulates the activity of aminophospholipid flippases via Fpk1 and Fpk2 kinases, and phospholipid asymmetry in plasma membranes (Roelants et al, 2010).…”
Section: Introductionmentioning
confidence: 99%